It Was the Best of Times, It Was the Worst of Times: Understanding the Relationship of Hassles and Depressive Symptoms in New Zealand Elite Athletes - Sara Winther; Ian de Terte; Warrick Wood; Sarah Beable; Kylie Wilson; Bruce Hamilton (Journal of Clinical Sport Psychology, 2025)
This study investigated the association between hassles and depressive symptoms in a sample of New Zealand elite athletes. It replicated the study undertaken by Beable et al. in 2017, although the same participants could not be resurveyed, the same constructs were measured. Data obtained from 126 elite athletes showed similar rates of depressive symptoms to rates previously recorded. However, findings highlighted an increase in the severity of depressive symptoms. Like the previous study, athletes competing in individual sports and younger athletes were at greater risk of experiencing depressive symptoms. Male athletes, those contemplating retirement, and individual athletes were associated with increased frequency and/or severity of hassles. Increased hassles were found to be a predictor of depressive symptoms. While findings indicate that the rates of elite athletes experiencing depressive symptoms stayed relatively consistent, particular groups of athletes remain vulnerable and should be the focus of targeted support measures.